GAYA BAHASA 10 GEGURITAN DALAM ANTOLOGI NURANI PEDULI KARYA HANDOYO WIBOWO - Ayu Warnaningrum; Sudartomo Macaryus (Universitas Sarjanawiyata Tamansiswa, 2015)
This study aims to assess the characteristics geguritan Handoyo Wibowo works in the anthologyÂ Conscience Care. This study aimed to describe (1) the characteristics of language author who studied through clause types and compaction language conducted by the author, (2) diction in geguritan-geguritan works Handoyo Wibowo, (3) sound, (4) imagery, and (5) figure of speech. The research is a qualitative descriptive. The data in this study are the types of clauses that are used in the anthology Geguritan, words (diction).Sumber data used in this study a book Anthology ofConscience Care geguritan work Handoyo Wibowo categorized as a document. The instrument used in this study is a set of books - books stylistic, syntactic structures, in particular, the clause, sound, diction, figure of speech, and imagery that became the theoretical basis in order to obtain better data. Provision of data in this study using an advanced simak.Teknik method used in this study are engineering and technical literature record. Data analysis methods used in this study is a translational agih and unified method. Data were analyzed using the technique of direct element.Advanced techniques used sorting technique decisive element is aggregated translational power engineering, power and power sorting aggregated referential orthography. Results of the study are (1) geguritan work there Handoyo Wibowo compaction akromin said that the title is a phrase or clause that is the meaning of that title. Geguritan entitled